MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI METODE CERAMAH INTERAKTIF (DI SMPT MATHLAUL KHAER) - salman khan, Salman Alfarizi; Yanto Maulana Restu; Abdul Rohim; Fitri Fatimatuh Azzahra (Program Studi Pendidikan Agama Islam, 2025)
Learning motivation is an important factor that influences students' success in understanding and mastering the subject matter. However, conventional lecture methods are often considered less effective in increasing learning motivation, because students only listen passively without much opportunity to be directly involved. Therefore, this study aims to explore the effectiveness of the interactive lecture method in increasing students' learning motivation. The interactive lecture method combines the delivery of material with participatory techniques, such as group discussions, questions and answers, case studies, and the use of visual media and interactive technology. The results of the study showed that the interactive lecture method can significantly increase student involvement, interest, and motivation. Students become more active in the learning process, so that their understanding and memory of the material also increase. Thus, the interactive lecture method is an effective alternative to increasing students' learning motivation in the classroom environment